Cyber Security and COVID-19 Pandemic : Muhammad Shairoze Malik - Malik, shairoze (International Journal for Electronic Crime Investigation, 2021)
This paper investigates the issues arisen as a result of COVID-19 pandemic in the domain of cyber security. Vulnerable people and systems have become a target of cyber criminals due to pandemic. This paper discusses an increase in cyber-attacks due to pandemic. Furthermore, the rate of cyber-attacks has been increased due to an increase in fear and anxiety caused by the pandemic. Healthcare organizations have become the primary targets of cyber-attacks during the pandemic. Many companies are expecting employees to work from home (WFH), which has also prompted concerns about cybersecurity and the risk of state-sponsored assaults, and a rise in ransomware and phishing attacks. This paper also offers many practical ways to minimize the dangers of cyber-attacks, while working from home. And also discusses mitigation of healthcare security concerns. It is critical that healthcare companies establish a comprehensive cybersecurity strategy to strengthen the security of their critical data and assets